2013
DOI: 10.1063/1.4788666
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive and comparative study of elastic electron scattering from OCS and CS2 in the energy region from 1.2 to 200 eV

Abstract: We report absolute differential cross sections (DCSs) for elastic electron scattering from OCS (carbonyl sulphide) and CS 2 (carbon disulphide) in the impact energy range of 1.2-200 eV and for scattering angles from 10 • to 150 • . Above 10 eV, the angular distributions are found to agree quite well with our present calculations using two semi-phenomenological theoretical approaches. One employs the independent-atom model with the screening-corrected additivity rule (IAM-SCAR), while the other uses the continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 69 publications
(126 reference statements)
1
25
1
Order By: Relevance
“…We note, however, that the present calculations revealed that contributions from the dipole moment, such as we found previously with OCS, 13 are only significant for scattered electron angles below 10 • , which were not experimentally accessed in the present measurements. Importantly, the shaper of those calculations were nonetheless sometimes used to help us obtain the elastic ICS in our extrapolation procedure.…”
Section: Theoretical Outlinecontrasting
confidence: 52%
See 2 more Smart Citations
“…We note, however, that the present calculations revealed that contributions from the dipole moment, such as we found previously with OCS, 13 are only significant for scattered electron angles below 10 • , which were not experimentally accessed in the present measurements. Importantly, the shaper of those calculations were nonetheless sometimes used to help us obtain the elastic ICS in our extrapolation procedure.…”
Section: Theoretical Outlinecontrasting
confidence: 52%
“…52 Moreover, this approach seems to be inherently suitable for electron scattering from a heavy-atom electron-rich molecule, such as GeF 4 , in which its application ranges down to ∼7 eV. 4 Furthermore, e.g., for the polar molecule OCS, 13 additional dipole-excitation cross sections can be calculated through the IAM-SCAR and rotational contribution method, 46, 53 which has been successfully used for other polar molecules such as H 2 O. 54 Thus, the range of validity of our approach may even be extended to energies possibly below 10 eV.…”
Section: Theoretical Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In a recent work on the elastic scattering from the halomethane-molecules, CH 3 F, CH 3 Cl, CH 3 Br, and CH 3 I, 24 we have shown for the first time atomic-like behavior of these scattering systems by comparing the elastic DCSs of these molecules with those for the corresponding noble gases, Ne, Ar, Kr, and Xe, respectively. Such behavior was soon after shown for other molecular systems as CCl 4 , 25 SiF 4 , 26 GeF 4 , 27 COS and CS 2 , 28 and C 4 F 6 isomers 29 scattering systems by comparison of the elastic DCSs for corresponding atomic chlorine, fluorine, and sulphur atoms in the intermediate impact energy region, respectively. Here, we also verify, for the first time, such atomic-like behavior in the electron scattering processes from XF 3 (X = B, C, N, and CH) molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42] Briefly, each atomic target (C, Cl, H) is represented by an interacting complex potential, the so-called optical potential. The real part accounts for the elastic scattering of the incident electrons, and the imaginary part represents the inelastic processes, which is considered as "absorption" from the incident beam.…”
Section: B Independent Atom Model Calculationsmentioning
confidence: 99%